A Proposal for Modernizing the Regulation of Human Biotechnologies - Furger, Franco (The Hastings Center report, 2007)
The technologies at the intersection of assisted reproduction and genetics call for a new regulatory approach, say Franco Furger and Francis Fukuyama, authors of the recent report Beyond Bioethics. In the essay below they map out their recommendation. In the following essays, James Fossett argues that regulation is likelier—and would be better—at the state level, Leonard Fleck calls for more robust public involvement, and John Robertson recommends sticking with the status quo. Turning from procedural to substantive issues, Josephine Johnston takes up Furger and Fukuyamas suggestion that children have a right to a traditional genetic parentage.